ABOUT THE MACHINERY (Intent Research Scientific Journal, 2023)
Technology (techne) is a framework of tools and skills that allow humans to influence the environment in order to obtain material wealth and meet the needs of people and society. The main task is to facilitate human labor and improve productivity. It allows you to make the most of natural resources, to absorb the Earth's throes, the world's oceans, and the cosmic space.